An unappreciated cell survival-independent role for BAFF initiating chronic lymphocytic leukemia - Ullah, Md Ashik; Garcillán, Beatriz; Whitlock, Eden; Figgett, William A.; Infantino, Simona; Eslami, Mahya; Yang, SiLing; Rahman, M. Arifur; Sheng, Yong H.; Weber, Nicholas; Schneider, Pascal; Tam, Constantine S.; et al. (Frontiers in Immunology, 2024)
Chronic Lymphocytic Leukemia (CLL) is characterized by the expansion of CD19 + CD5 + B cells but its origin remains debated. Mutated CLL may originate from post-germinal center B cells and unmutated CLL from CD5 + mature B cell precursors. Irrespective of precursor types, events initiating CLL remain unknown. The cytokines BAFF and APRIL each play a significant role in CLL cell survival and accumulation, but their involvement in disease initiation is unclear. Using the TCL1-transgenic (Tg) model of CLL, we have demonstrated that BAFF, but not, APRIL is needed for the initiation and dissemination of CLL cells. In the absence of BAFF or its receptor BAFF-R, expression of the TCL1 transgene is only able to increase CLL cell numbers in the peritoneal cavity without dissemination into the periphery.BAFF binding to BAFF-R is not required for peritoneal CLL cells survival but needed to activate a tumor-promoting gene program in these cells, possibly linked to CLL initiation of progression. Our work on both mouse and human CLL cells suggests that BAFF might initiate CLL through cell survival-independent mechanisms. Combining current CLL therapies with BAFF inhibition may have a dual benefit: reducing peripheral tumor burden and suppressing transformed CLL cell output.